Epigenetic responses in juvenile Lemon sharks (Negaprion brevirostris) during a coastal dredging episode in Bimini, Bahamas. (August 2021) - Paige Beal, Andria; Hackerott, Serena; Franks, Bryan; Gruber, Samuel H; Feldheim, Kevin; Eirin-Lopez, Jose M
Highlights: DNA methylation and metals were quantified in response to a dredging event. Changes in DNA methylation pattern were found in exposed group. Environmental fit of metals found a correlation to the DNA methylation pattern. Advantages and limitations of this approach are identified and discussed. MSAP is a promising method for affordable long-term monitoring and assessment. Abstract: Sharks serve as key predators in coastal areas, with several species using near shore habitats as nursery refuges. With many shark species threatened or endangered, it is now critical to increase the knowledge of how anthropogenic activities impact these populations. This study is the first attempt at characterizing epigenetic modifications in elasmobranchs, and their potential as biomarkers of stress and disease using a dredging event episode in the early 2000′s in Bimini, Bahamas, as a model system. Lemon shark fin samples were selected from a historic archive (1995–2012) of Bimini's North (impacted) and South (control) shark nurseries, and classified as before (1995–2000), during (2001–2006), and after (2007–2012) the dredging event. Genome-wide DNA methylation was analyzed in these samples, along with the quantification of trace metals to investigate temporal and spatial patterns of metal concentrations. The obtained results revealed differential DNA methylation patterns in sharks from the North nursery (closest to the dredging site). While low concentrations of metals were found for all nursery sites and time frames, one trace metal (Manganese) was significantly correlated with the observed differences in DNA methylation. Overall, the findings of this study support DNA methylation as a potential stress biomarker for sharks, even in the absence of a reference genome. Furthermore, the identification of genomic regions differentially methylated in response to stress provides a basis for future analyses aimed at identifying gene networks and subsequent physiological responses to these events. Collectively, these analyses will help improve shark population monitoring, management, and conservation in impacted areas.